Effect Emotional Demontrasion (Emo Demo) Of Complementary Knowledge Foods ( Complementary Feeding) Of Mothers With Children Unders Two Years Old Under Two Years Old - Ravi Masitah; Diah Tri Andini; Siti Soleha (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background : The nutritional needs of children under two years old (Baduta) can be completed by consuming complementary feeding because nutritional needs cannot be completed only from breast milk. The impact of early complementary feeding can cause diarrhea and can cause death in infants. Mothers must have good knowledge. Emo demo is an intervention method that can increase knowledge related to complementary feeding. Aim : the aim of this study is to determine the effect of the Emotional Demontration (Emo demo) method of complementary feeding on the knowledge of mothers with children under two years old (Baduta). Methods : This research is descriptive analytical research with a quasi- experimental reasearch design One Group Pre Test and Post Test Design. The number of subjects in this study was 33 mothers who had children under two years old. The variables analyzed inclued family characteristic (respondent, age, mothers education, mothers occupation, fathers occupation, family income, and number of children). Results : the results of the analysis showed that there is effect of the emo demo intervention method wuth changes in knowledge with p-value <0,05. Conclusion : increased knowledge can affect mothers ability to give complementary feeding Keywords : Children Under Two Years Old, Complementary Feeding, Emo Demo Method